Theodore B. Bronson papers - Bronson, Theodore B.
Volume containing letters from Bronson to other Union Army officers, concerning the recruitment of soldiers, enlistment bounties, and desertion during the Civil War.
U.S. army officer.
Collection material in English.
Keywords: United States. -- Army -- Officers; United States. -- Army -- Recruiting, enlistment, etc. -- Civil War, 1861-1865.; Bounties, Military; Desertion, Military; United States -- History -- Civil War, 1861-1865.; Army officers